Comparing the effectiveness, safety and tolerability of interventions for depressive symptoms in people with multiple sclerosis: a systematic review and network meta-analysis protocol. Issue 6 (9th June 2022) - Lyons, Julia; Campese, Stephanie; Learmonth, Yvonne C; Metse, Alexandra; Kermode, Allan G; Karahalios, Amalia; Marck, Claudia H
Abstract : Background: Comorbid depression is prevalent in people with multiple sclerosis (MS). Depression is commonly untreated or undertreated, thus, there is a need for effective and safe interventions and current guidelines recommend psychological and pharmaceutical interventions for people with MS. However, research suggests that other interventions, such as exercise, could also be effective. The comparative efficacy and safety of intervention modalities have not been quantified. We plan to conduct a systematic review and network meta-analysis to compare efficacy and safety of psychological, pharmaceutical, physical and magnetic stimulation interventions for depression in people with MS. Methods and analysis: We will search EMBASE, Medline, Cochrane CENTRAL, APA PsycINFO, Web of Science, CINAHL and PEDro from inception to 31 December 2021. Search terms will stem from three concepts: MS, depression and randomised controlled trials. Included studies will be randomised controlled trials, where participants are people with MS randomised to receive one of the aforementioned intervention types, and depression or depressive symptoms is the primary outcome, only outcome or secondary outcome with an a priori power calculation. Screening, data extraction and risk of bias assessment (using the Risk of Bias 2 tool) will be conducted independently by two reviewers. If possible, we will synthesise the evidence by fitting a frequentist network meta-analysis model with multivariate random effects, or a pairwise random-effects meta-analysis model. For each model, efficacy will be measured using a standardised mean difference, and safety using an OR. We plan to provide summary measures including forest plots, a geometry of the network, surface under the cumulative ranking curve, and a league table, and perform subgroup analyses. Otherwise, a narrative review will be provided. Ethics and dissemination: Ethics is not required for a systematic review and network meta-analysis. Results will be published in a peer reviewed journal. PROSPERO registration number: CRD42020209803.